Feasibility analysis of oil palm harvesting using fiber laser system - Azaman, Mohd Ikmal Hafizi (2019)
Malaysia is currently experiencing a labour shortage in oil palm plantations, estimated to account for 46 % of the total industrial workforce. The industry is striving to increase worker productivity by adopting new technologies using a variety of work methods. One of the possibilities is laser cutting technology. Experimental design and methodology of developing a pulsed-fiber laser for cutting oil palm fronds had been discussed in this chapter. The main idea was to characterize and optimize the quality of the laser cutting using two different focus lenses i.e. 250 mm and 63 mm and a jig holder. This section focuses on characterizing the laser beam that was produced and its quality in cutting frond samples by looking at speed of laser beam (mm s-1), frequency (kHz), power (%), and time taken to complete the task of cutting. The results indicated the best cutting speed was at a speed of 1 mm s-1 with the optimum of frequency is 5000 kHz. In this research, the optimum cutting power was 50W, which was equivalent to 2 mJ of energy. Under this optimum condition, the time taken to cut fronds was 3 – 5 minutes. It can be concluded that the pulsed fiber laser technology can cut bio-materials such as oil palm frond. However, to declare it as one of the harvesting methods still require further investigations owing to its power limitation that cannot reach the standard time of harvesting.